Использование ферментов обмена пуриновых оснований для мониторинга загрязнения окружающей среды - Г. Г. Семерджян; Г. А. Семерджян (ՀՀ ԳԱԱ հրատ.)
Нами изучалось влияние ионов тяжелых металлов (Cu++, Cd++) на активность адениндезаминазы у 4 представителей моховидных Pellia epiphilla (L.) Lindb, Tortula ruralis (Hedw) Crome, Brym capillare Hedw, Brachythecium campestre (Bruch) B.S.G. Из полученных данных можно сделать вывод, что тяжелые металлы даже в незначительных концентрациях влияют на активность фермента адениндезаминазы. Morphological and physiological properties of mosses, along with their wide distribution make these plants very popular bioindicators to assess the state of the environment. Mosses are most effective at concentrating heavy metals and other trace elements. The process of deamination of adenine in homogenates of mossy plants of the family Bryophyta, Bryaceae, Brachythecium campestre was investigated. The effect of metal ions (Cu++, Cd++) for activity of studied enzymes. The ions Cu++, Cd++ inhibit the activity of investigated enzyme. Ուսումնասիրվել են մամուռների Bryophyta, Bryaceae, Brachythecium ընտանիքների ներկայացուցիչների մոտ ադենին դեզամինազ ֆերմենտի ակտիվության վրա, ծանր մետաղների (Cu+, Cd++) իոնների ազդեցության պայմաններում: Բացահայտվել են որոշ օրինաչափություններ տարբեր մետաղների ազդեցության և մամռանմանների տարբեր ներկայացուցիչների վրա:
Keywords: Biology; Ecology